Rancang Bangun Peralatan Uji Karakteristik Pompa Sentrifugal Susunan Seri dan Paralel untuk Pembelajaran Sistem Pompa dan Perpipaan - Hendra Saputra (Politeknik Negeri Batam, 2020)
In shipping industry, especially on ships, centrifugal pumps are used in piping systems. Pumps are the most component used for fluid transferring process of piping systems such as ballast systems, bilga systems, fire fighting systems, sanitary systems, fresh water systems and engine cooling systems. The used of pump capacity may varies depending on system requirements. On pump operation, especially centrifugal pumps can be used as a single, series, or parallel according to flow requirements and working pressure (pressure head). The characteristics of centrifugal pumps that are operated in series and parallel can be known through direct pump operation or can be done through the use of a visual aid. The pump operation trainer is designed as a learning aids to determine the characteristics of series and parallel centrifugal pumps. The purpose of this research is to design a model of test equipment for the characteristics of a series and parallel arrangement of centrifugal pumps. The research method is carried out in several stages such as designs, build and testing This research also made a plans for further development of automatic control and monitoring systems